"Is That All There Is?": Time, Guilt, and Melancholia in Sleep No More and Macbeth. (31st January 2014) - Churchill, Christian J.; Gilligan, James
Abstract This paper uses the interactive performance play Sleep No More and William Shakespeare's Macbeth as bases for exploring the experience of depressive stasis. Freud's "Mourning and Melancholia" is used as a means of interpreting these works. Through the dramatic portraits of the self turned destructively upon itself found in these plays, psychoanalysis is offered as a way of imagining how grief and loss can be experienced as annihilating rather than transformative. At the core of Freud's essay is the idea that for the melancholic, time feels stuck. This paper posits that Sleep No More and Macbeth illuminate how we can think about patients in this condition and how we might try to grasp their experience of feeling like time has stopped and that hope is therefore lost. Copyright © 2014 John Wiley & Sons, Ltd.